2003
DOI: 10.1177/147323000303100207
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Prednisolone and Serum Malondialdehyde Levels in Puppies with Experimentally Induced Meconium Aspiration Syndrome

Abstract: The aim of this study was to investigate the effect of different doses of prednisolone in puppies experimentally induced with meconium aspiration syndrome (MAS). Meconium was collected from human babies in the first day of life and was released into the trachea of 11 newborn puppies to induce MAS. Puppies were treated with 2 mg/kg prednisolone (standard dose), 30 mg/kg prednisolone (megadose) or 0.9% saline, all administered intravenously. The study ended 20 h after meconium aspiration and the lungs were then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Pretreatment with methylprednisolone 30 minutes before meconium instillation decreased levels of ET-1 and thereby decreased pulmonary vascular resistance, intrapulmonary shunting, and lung edema formation and improved oxygenation [119]. Reduced physiological and histological lung injury changes after intravenous prednisolone were shown also in meconium-instilled puppies, with better results on higher dose [122]. Similarly, pretreatment and early treatment with intravenous dexamethasone increased lung compliance, and reduced pulmonary vasoconstriction resulting in better oxygenation [118,123].…”
Section: Corticosteroidsmentioning
confidence: 77%
“…Pretreatment with methylprednisolone 30 minutes before meconium instillation decreased levels of ET-1 and thereby decreased pulmonary vascular resistance, intrapulmonary shunting, and lung edema formation and improved oxygenation [119]. Reduced physiological and histological lung injury changes after intravenous prednisolone were shown also in meconium-instilled puppies, with better results on higher dose [122]. Similarly, pretreatment and early treatment with intravenous dexamethasone increased lung compliance, and reduced pulmonary vasoconstriction resulting in better oxygenation [118,123].…”
Section: Corticosteroidsmentioning
confidence: 77%
“…In the study by Kirimi et al [39], the intravenous administration of prednisolone at standard (2 mg/kg) and high (30 mg/kg) doses immediately after meconium instillation improved gas exchange and increased the frequency of breathing in meconium-instilled puppies in comparison with the non-treated group. In addition, high-dose prednisolone showed a more obvious improvement in lung histology compared to the standard dose, without hyperglycaemia or hypertension as side effects.…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…However, high-dose prednisolone significantly increased the plasma levels of malonyldialdehyde, product of lipid peroxidation, compared to standard-dose group and controls at 20 h after meconium aspiration. It may suggest a paradoxically lower effectivity of high-dose vs. standard-dose prednisolone in the reduction of oxidation stress resulting from inflammation or even the potentiation of oxidation stress by a mega-dose of prednisolone [39]. Nevertheless, the value of this information is limited by the small number of animals included in the treated groups ( n  = 3 each).…”
Section: Glucocorticoidsmentioning
confidence: 99%
“…Severe pulmonary oedema was noticed in these animals, perhaps due to the mineralocorticoid action of hydrocortisone 15 . Kirime E et al 16 revealed high dose IV methyl prednisolone produced more clinical benefit when compared to the standard dose but with increased risk of oxidative stress in puppies. The main advantage with budesonide was the route of administration.…”
Section: Discussionmentioning
confidence: 99%